Implementing a Reference Measurement System for C-Peptide: Successes and Lessons Learned. (1st September 2017) - Little, Randie R; Wielgosz, Robert I; Josephs, Ralf; Kinumi, Tomoya; Takatsu, Akiko; Li, Hongmei; Stein, Daniel; Burns, Chris
Abstract: BACKGROUND: Assessment of endogenous insulin secretion by measuring C-peptide concentrations is widely accepted. Recent studies have shown that preservation of even small amounts of endogenous C-peptide production in patients with type 1 diabetes reduces risks for diabetic complications. Harmonization of C-peptide results will facilitate comparison of data from different research studies and later among clinical laboratory results at different sites using different assay methods. CONTENT: This review provides an overview of the general process of harmonization and standardization and the challenges encountered with implementing a reference measurement system for C-peptide. SUMMARY: Efforts to harmonize C-peptide results are described, including those by the National Institute of Diabetes and Digestive and Kidney Diseases–led C-peptide Standardization Committee in the US, activities in Japan, efforts by the National Institute for Biological Standards and Control in the UK, as well as activities led by the Bureau International des Poids et Mesures and the National Metrology Institute in China. A traceability scheme is proposed along with the next steps for implementation. Suggestions are made for better collaboration to optimize the harmonization process for other measurands.